Energy endowments, barriers to trade and industry location in Chinese provinces - Irina Hotz (University of Neuchâtel, Institute of Economic Research (IRENE), 2012)
This study analyzes the determinants of manufacturing activity across Chinese provinces with emphasis on the important role of energy endowments on the location of industries. The data set consists of a panel of 28 Chinese provinces and 13 manufacturing industries for the years 1994, 1997 and 1999-2009. A model of production location is estimated, including comparative advantage and economic geography dynamics. The effects of trade impediments and changes in economic policies on the distribution of economic activity are also considered. Results validate energy as a driving force of industry location. They further show that provincial protectionism poses a problem to market mechanisms, but indicate an increase of concentration of economic activity through time.
Keywords: F18; P2; R14; 330; China; factor endowments; industry location; energy; externalities; protectionism